1988
DOI: 10.17161/fec.v21i3.7510
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Classrooms Through Levels Systems

Abstract: The implementation oflevels systems has recently increased in public school programs for students with behavioral disorders. These systems, emerging from residential and treatment programs for students with complex behavioral disorders, have been applied with adolescents involved in substance abuse (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…As noted by Fantuzzo, Polite, Cook, and Quinn (1988), higher degrees of student self-management are related to greater treatment effects. As students progress through the levels, the teacher's role becomes less directive and more facilitative (Bauer & Shea, 1988). Also, level systems direct a student toward greater degrees of mainstreaming and self-discipline as they progress to higher levels.…”
Section: Definition and Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…As noted by Fantuzzo, Polite, Cook, and Quinn (1988), higher degrees of student self-management are related to greater treatment effects. As students progress through the levels, the teacher's role becomes less directive and more facilitative (Bauer & Shea, 1988). Also, level systems direct a student toward greater degrees of mainstreaming and self-discipline as they progress to higher levels.…”
Section: Definition and Rationalementioning
confidence: 99%
“…In addition to regular levels that students will progress through, Bauer and Shea (1988) also have suggested that a disciplinary level be determined. Students having particular difficulty over a short period of time can be removed temporarily from their present level and be placed on a more restrictive disciplinary level.…”
Section: Characteristics Of a Level Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The best behavior management system for these purposes is a structured management program based on behavioral principles (Center, 1989a;Center & McKittrick, 1987;Kazdin, 1977). An important part of such a program is a levels system (Bauer & Shea, 1988) to facilitate weaning the student from the imposed structure, increase delay of gratification, enhance self-evaluation skills, and promote control by natural reinforcers.…”
Section: Behavioral Managementmentioning
confidence: 99%